2014
DOI: 10.5194/amt-7-3059-2014
|View full text |Cite
|
Sign up to set email alerts
|

An inverse-modelling approach for frequency response correction of capacitive humidity sensors in ABL research with small remotely piloted aircraft (RPA)

Abstract: Abstract. The measurement of water vapour concentration in the atmosphere is an ongoing challenge in environmental research. Satisfactory solutions exist for ground-based meteorological stations and measurements of mean values. However, carrying out advanced research of thermodynamic processes aloft as well, above the surface layer and especially in the atmospheric boundary layer (ABL), requires the resolution of small-scale turbulence. Sophisticated optical instruments are used in airborne meteorology with ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…The sensor P14 has been well investigated in Wildmann et al [42], where a technique has been shown to reconstruct water vapor on the sensor surface by taking advantage of physical modeling. Furthermore, the limitations of this technique have been shown in Wildmann et al [42].…”
Section: Post-processing Of Humidity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensor P14 has been well investigated in Wildmann et al [42], where a technique has been shown to reconstruct water vapor on the sensor surface by taking advantage of physical modeling. Furthermore, the limitations of this technique have been shown in Wildmann et al [42].…”
Section: Post-processing Of Humidity Measurementsmentioning
confidence: 99%
“…Furthermore, the limitations of this technique have been shown in Wildmann et al [42]. Because of these limitations, again a first order transfer function for humidity measurements is assumed, and ascents and descents were compared to determine time constants.…”
Section: Post-processing Of Humidity Measurementsmentioning
confidence: 99%
“…After applying this function to the reference RH liquid time series, the ICH time series is reproduced for almost the complete cold flight sequence without getting worse in the warmer sequence of the flight. The remaining deviations might have their origins in calibration uncertainties, as well as in the potential deviations in the response time for conditions when the RH liquid is either increasing or decreasing (Wildmann et al, 2014) and uncertainties in the reference measurement.…”
mentioning
confidence: 99%
“…The overall endurance achieved with MASC is up to 90 min, which is associated with a flight distance of 135 km. MASC is standardly equipped with several subsystems specifically to measure the wind vector in three dimensions with a five-hole probe [35], air temperature with fast fine-wire probes [36], and humidity [37] with a capacitive sensor. The measurement equipment is able to resolve wind and temperature fluctuations up to 30 Hz and humidity fluctuations up to 3 Hz, all sampled with a rate of 100 Hz.…”
Section: Description Of Measurementsmentioning
confidence: 99%